CREST-iMAP v1.0: A fully coupled hydrologic-hydraulic modeling framework dedicated to flood inundation mapping and prediction. (July 2021) - Li, Zhi; Chen, Mengye; Gao, Shang; Luo, Xiangyu; Gourley, Jonathan J.; Kirstetter, Pierre; Yang, Tiantian; Kolar, Randall; McGovern, Amy; Wen, Yixin; Rao, Bo; Yami, Teshome; et al.
Abstract: Under the impacts of hydrologic extremes, there is a growing need for integrated frameworks for flood inundation mapping. In this study, we introduce a framework: the Coupled Routing and Excess Storage for inundation MApping and Prediction (CREST-iMAP). It utilizes a highly parallelized and fully integrated hydrologic-hydraulic model and aims to improve flood prediction. To highlight the advantages, a synthetic rainfall event and the 500-year Hurricane Harvey event were investigated using the CREST-iMAP, compared with a hydrologic model, a hydraulic model, and a simplified hydrologic-hydraulic model. The results indicate the CREST-iMAP achieves good performances in both hydrologic simulation and floodplain inundation mapping. Moreover, the antecedent soil moisture is the most sensitive parameter to model accuracy, followed by the land surface characteristics; the infiltration process to a flood forecasting model is significant. Overall, the CREST-iMAP delivers accurate and timely flood information, making it one of the latest developments of an integrated hydrologic-hydraulic expert system. Highlights: A fully coupled hydrologic & hydraulic modeling framework is developed for both riverbank flow and overland flood inundation. The sensitivities of model parameters are quantified and constrained with respect to basin attributes. Hydrologic infiltration process is central for improving both the streamflow simulation and flood inundation mapping. The CREST-iMAP framework achieves good performances in both hydrologic simulation and floodplain inundation mapping.